Carbon and nitrogen stable isotope signatures reveal constraints to nutritional modes in orchids from the Mediterranean and Macaronesia. - Liebel,HT; Bidartondo,MI; Preiss,K; Segreto,R; Stockel,M; Rodda,M; Gebauer,G (AM J BOT, 2010)
We compared the nutritional modes and habitats of orchids (e.g., autotrophic, partially or fully mycoheterotrophic) of the Mediterranean region and adjacent islands of Macaronesia. We hypothesized that ecological factors (e.g., relative light availability, surrounding vegetation) determine the nutritional modes of orchids and thus impose restrictions upon orchid distribution. Covering habitats from dark forests to open sites, orchid samples of 35 species from 14 genera were collected from 20 locations in the Mediterranean and Macaronesia to test for mycoheterotrophy. Mycorrhizal fungi were identified via molecular analyses, and stable isotope analyses were applied to test whether organic nutrients are gained from the fungal associates. Our results show that orchids with partial or full mycoheterotrophy among the investigated species are found exclusively in Neottieae thriving in light-limited forests. Neottioid orchids are missing in Macaronesia, possibly because mycoheterotrophy is constrained by the lack of suitable ectomycorrhizal fungi. Furthermore, most adult orchids of open habitats in the Mediterranean and Macaronesia show weak or no N gains from fungi and no C gain through mycoheterotrophy. Instead isotope signatures of some of these species indicate net plant-to-fungus C transfer.